(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3GHQGgje Hf eMeO Hf eMeO GdOcGdi s)
(3ChdgG (B:s
(3jHOC GdehLhO efgG HeGg Mhe (B: (3MGe GdWjQ hZjQg Mhd GdTF s
(3fSNI NGeSI YTQIs
(3jJNddgG ChQGb HNW eZQHis
(3jJab BNQgG eY BNQ fSNI YGQa MceJ (B- 28 (3dZI HGNJdGa ai HYV GdCdaGXs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs